2022
DOI: 10.1002/trc2.12247
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pimavanserin on psychotic phenotypes and tau phosphorylation in the P301L/COMT– and rTg(P301L)4510 mouse models of Alzheimer's disease

Abstract: Introduction Psychosis in Alzheimer's disease (AD) is associated with grave clinical consequences including a precipitous cognitive decline and a hastened demise. These outcomes are aggravated by use of existing antipsychotic medications, which are also associated with cognitive decline and increased mortality; preclinical models that would develop new therapeutic approaches are desperately needed. The current report evaluates the ability of the neoteric antipsychotic, pimavanserin, to normalize hyperkinesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Mice were kept on a reverse light/dark 12 h cycle, and testing was performed in a sound-attenuated room. In order to evaluate the effects of dopaminergic and cholinergic neuropharmacology on behavior and neurophysiology, we utilized P301L/COMTKO [ 58 ] mice developed in our lab, which express a human mutation (P301L) in the microtubule-associated protein tau ( MAPT ) gene that causes frontotemporal dementia and Parkinsonism linked to chromosome 17 (FTDP-17), resulting in motor and behavioral deficits in mice driven by neurofibrillary tangle pathology [ 56 ] in the context of the deletion of the COMT gene [ 55 ]. P301L/COMTKO mice were bred and maintained at the Center for Comparative Physiology in the FIMR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were kept on a reverse light/dark 12 h cycle, and testing was performed in a sound-attenuated room. In order to evaluate the effects of dopaminergic and cholinergic neuropharmacology on behavior and neurophysiology, we utilized P301L/COMTKO [ 58 ] mice developed in our lab, which express a human mutation (P301L) in the microtubule-associated protein tau ( MAPT ) gene that causes frontotemporal dementia and Parkinsonism linked to chromosome 17 (FTDP-17), resulting in motor and behavioral deficits in mice driven by neurofibrillary tangle pathology [ 56 ] in the context of the deletion of the COMT gene [ 55 ]. P301L/COMTKO mice were bred and maintained at the Center for Comparative Physiology in the FIMR.…”
Section: Methodsmentioning
confidence: 99%
“…While the tauopathy of AD has been well characterized, as there are no known autosomal dominant mutations in the microtubule-associated protein tau ( MAPT ) gene that are associated with familial AD, transgenic models that express mutant forms of human tau, associated with frontotemporal dementia [ 52 ], have been employed to study outcomes with relevance to the disease [ 53 ]. Our previous studies suggest that total tau and pathogenic phosphotau species disrupt PPI in the rTg(P301L)4510 model of tauopathy [ 54 ], and increases in tau expression may be associated with changes in locomotion [ 55 ]. We have developed a preclinical tau model of psychotic AD, expressing the P301L human mutant tau gene associated with human tauopathy [ 56 ], together with the deletion of the catechol-o-methyltransferase gene (COMT), in order to drive dopamine neurotransmission [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tripterygium glycoside (TG) improves spatial memory and learning abilities, reduces the expression of AB25-35, p-Tau, and CD11b, increases neuron density, and suppresses the release of inflammatory factors and microglial activity by inhibiting the phosphorylation of IκBα and p38 MAPK, thus alleviating neuroinflammation in a mouse model of Aβ25-35-induced AD [ 102 ]. Pimavanserin restored normal locomotion in both the P381L/COMT- and rTg(P301L)4510 mouse models of AD, without affecting sensorimotor gating or tau phosphorylation patterns, indicating that pimavanserin may alleviate excessive locomotion driven by tau [ 103 ]. Hoon Lim et al explored the use of human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) to inhibit tau hyperphosphorylation and discovered that hUCB-MSCs can alleviate tau hyperphosphorylation by secreting GAL-3, revealing their potential as a therapeutic agent for abnormal tau in AD [ 104 ].…”
Section: Treatment Strategy Based On Pptmsmentioning
confidence: 99%
“…We compared the acute effects in JNPL3 (P301L) mice, which express the mutant human tau associated with autosomal dominant tauopathy (Lewis et al 2000), to COMTKO/P301L mice, which have impaired dopamine metabolism (Koppel et al 2019). Our group demonstrated that the COMTKO/ P301L mice have dopamine-driven increases in tau phosphorylation relative to P301L mice (Jimenez et al 2022). The degree of baseline tau hyperphosphorylation could be critical in determining the impact of anesthesia on the subsequent tau aggregation that may be relevant for post-operative cognitive decline.…”
mentioning
confidence: 99%